Innovation through Delivery of Tacit-Explicit Knowledge: A Maqasid Approach - Arman, Hj. Ahmad; Ridzuan, Masri; Rana, Altounjy; Siti Haryani, Mat Yusof; Normy Rafida, Abdul Rahman; Mohd. Farid, Shamsudin (2021)
Innovation plays an important role in generating progress through transformation and improvement. It begins at the earliest stage of the process, which is knowledge delivery. Explicit knowledge is the most significant knowledge delivered before innovation can take place. While tacit knowledge has no significant role due to its nature of being very difficult to measure its effectiveness. Tacit knowledge is identified as one of the main elements for the delivery of knowledge towards innovation. However, innovation through the most efficient tacit-explicit knowledge can still leave the adverse effect, if no boundary lines are determining how innovations take place. The present study has employed a qualitative research design using the hermeneutic approach to propose Islamic innovation through the maqasid shari’ah approach in the context of knowledge delivery, as the initial process in innovation.